164k views
3 votes
Write an expression that is equivalent to 5(t+3) .

User Derwiwie
by
5.7k points

2 Answers

4 votes

Answer: 5t+15

This is equivalent to 5t+5*3

To get the answer, you multiply the outer term 5 by each term inside

5 times t = 5*t = 5t

5 times 3 = 5*3 = 15

Then you add up those products to get 5t+15.

This is using the distributive property.

User EvR
by
5.9k points
4 votes

Answer: 5t+15

Step-by-step explanation: Distribute the 5 into the parenthesis.

5 x t = 5t

5 x 3 = 15

You will get 5t +15.

User Place
by
5.5k points